2017
DOI: 10.4172/2329-6607.1000229
|View full text |Cite
|
Sign up to set email alerts
|

Impervious Coronary No-Reflow: A Case Study

Abstract: Coronary no-reflow phenomenon is a disorder of the microvasculature that results in poor myocardial perfusion in patients with acute myocardial infarction receiving percutaneous coronary intervention. It typically manifests as TIMI 1-2 flow, high TIMI frame counts, and abnormal myocardial blush. The etiology of this condition is multifactorial and so is its treatment. It is encountered in approximately one-third of patients and is therefore of clinical relevance. In this case report, we describe a patient scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, despite these technical improvements, no‐reflow phenomenon is still a challenging complication during PCI 3,4 . Previous studies have shown that no‐reflow phenomenon is identified in approximately 2% of patients undergoing PCI 4–6 . The hypotheses and mechanisms of no‐reflow phenomenon are multifactorial, including micro‐embolization, coronary dissection, microvascular dysfunction, reperfusion injury, and vasospasm 7–9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite these technical improvements, no‐reflow phenomenon is still a challenging complication during PCI 3,4 . Previous studies have shown that no‐reflow phenomenon is identified in approximately 2% of patients undergoing PCI 4–6 . The hypotheses and mechanisms of no‐reflow phenomenon are multifactorial, including micro‐embolization, coronary dissection, microvascular dysfunction, reperfusion injury, and vasospasm 7–9 .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Previous studies have shown that no-reflow phenomenon is identified in approximately 2% of patients undergoing PCI. [4][5][6] The hypotheses and mechanisms of no-reflow phenomenon are multifactorial, including micro-embolization, coronary dissection, microvascular dysfunction, reperfusion injury, and vasospasm. [7][8][9] However, there are still no definitive hypotheses and mechanisms for the no-reflow phenomenon and it remains a subject of controversy.…”
mentioning
confidence: 99%